Exploring the knowledge and perception of generic medicines among final year undergraduate medical, pharmacy, and nursing students in Sierra Leone: A comparative cross-sectional approach - James, Peter Bai; Bah, Abdulai Jawo; Margao, Emmanuel Kamanda; Hanson, Christian; Kabba, John Alimamy; Jamshed, Shazia Qasim (MDPI, 2018)
Most low-income nations have national medicine policy that emphasized the use of generic medicines in the public health sector. However, the use of generics is often debatable as there are concerns over its efficacy, quality, and safety compared to their branded counterparts. This study was conducted to compare the knowledge and perception of generic medicines among final year undergraduate medical, pharmacy, and nursing students in Sierra Leone. We conducted a questionnaire-based cross-sectional study among these students at the College of Medicine and Allied Health Sciences University of Sierra Leone. Out of the 62 students, only two (2/62, 3.2%) knew about the acceptable bioequivalence limit. At least half of respondents in all three groups agreed that all generics are therapeutically equivalent to their innovator brand. At least half of the medicine (21/42, 50%) and nursing (6/9, 66.6%) students, compared to pharmacy students (5/11, 45.5%), believed that higher safety standards are required for proprietary medicines than for generic medicines. Most of them agreed that they need more information on the safety, quality, and efficacy aspects of generics (59/62, 95.2%). All three groups of healthcare students, despite variations in their responses, demonstrated a deficiency in knowledge and misconception regarding generic medicines. Training on issues surrounding generic drugs in healthcare training institutions is highly needed among future healthcare providers in Sierra Leone.